The Impact of Augmented Reality on Online Shopping Experience, Purchase Decision, and Customer Satisfaction in Modern E-Commerce Platforms - Sudirwo, Sudirwo; Safier Ramdani; Sezen Fetullah Mursalova (Management Dynamics: International Journal of Management and Digital Sciences, 2024)
Augmented Reality (AR) technology has emerged as a transformative tool in the e-commerce industry, enhancing the online shopping experience by offering interactive and immersive features. This study explores the impact of AR on consumer behavior, focusing on key factors such as trust, satisfaction, purchase decisions, and customer loyalty. Through a user experiment, participants interacted with AR-integrated e-commerce platforms, testing features such as virtual try-ons and product visualizations in real-world contexts. The results revealed that AR significantly enhances consumer trust, with more realistic and accurate product visualizations increasing confidence in both the product and platform. Customer satisfaction was also notably higher after interacting with AR features, with users reporting a more engaging and enjoyable shopping experience. Furthermore, purchase intention was positively influenced by the ability to visualize products and receive real-time, interactive feedback. Repeated exposure to AR led to increased customer loyalty, as participants expressed a higher likelihood of returning to use AR tools in future shopping experiences. These findings suggest that AR provides a strong competitive advantage for e-commerce platforms, enabling them to differentiate themselves in a crowded market by offering personalized, engaging, and trust-building shopping experiences. This research also highlights the practical implications for e-commerce businesses, recommending the integration of user-friendly and interactive AR features to enhance engagement, satisfaction, and decision-making. Future research should explore the broader applications of AR across industries and consumer segments to further understand its potential to revolutionize online shopping.